Poverty, Entitlement Approach, and the Program of Health Insurance for the Poor in Indonesia - SUTIYO, SUTIYO; RIYANI, ONDO; MELTARINI, MELTARINI (Universitas Muhammadiyah Yogyakarta, 2018)
This study analyzes the implementation of the Program of Health Insurance for the Poor in Indonesia, focusing at the advantages and constraints faced by the beneficiaries, through a case study in Purbalingga District. By applying the approach of entitlement within the framework of healthcare access, it is found that the program brings positive impacts in increasing financial abilities of the beneficiaries, and creating good treatment from the medical workers. Yet, low supply side readiness of health infrastructure and service system dilutes the benefits of the program in poverty alleviation. The government of Indonesia is recommended to involve communities and local officers in the enumeration of the beneficiaries, to increase the participation of private healthcare providers in the program, and to establish clear rewards and punishment system for the health workers.